Inovasi Pembelajaran Sosial Emosional Melalui Regulasi Emosi - Hamdani, Cindy Gusvita (Jurnal Pendidikan Tuntas, 2026)
This research explores the importance of integrating Social Emotional Learning (SEL) into primary education through the reflective practices of pre-service teachers within the Teacher Professional Education Program (PPG). The primary focus of this study is to analyze how the application of emotional regulation strategies can create a conducive learning atmosphere and improve the quality of students' character holistically. The research method employed is library research, examining the CASEL concepts and their practical implementation in mathematics learning for fourth-grade elementary school students. The discussion results indicate that structured social-emotional learning, executed with a contextual approach, serves as a significant innovation in enhancing educational quality. The use of innovative techniques such as the "Feeling Box," ice breaking, and the STOP mindfulness technique has proven effective in supporting student focus and engagement in the classroom. These strategies provide space for students to recognize, evaluate, and manage their emotions positively during the teaching and learning process. The research findings confirm that teachers act not only as academic facilitators but also as crucial emotional companions in building student resilience. Through integrated reflection and feedback, SEL is capable of creating a school ecosystem that is safe, enjoyable, and empowering. In conclusion, strengthening social-emotional competence for pre-service teachers is urgent to realize an education that balances cognitive intelligence and emotional maturity. This study provides significant implications for the development of a curriculum that is more responsive to the psychological well-being of students in elementary schools.